Clinical course involving thrombocytosis and thrombocytopenia in a patient with bladder cancer treated with gemcitabine and cisplatin. Issue 12 (5th December 2021) - Watanabe, Ayako; Momo, Kenji; Tanaka, Katsumi; Nagata, Takuya; Kuchira, Remi; Morita, Masashi; Sasaki, Tadanori
Abstract : Gemcitabine induce thrombocytopenia and thrombocytosis as toxicity. In this report, we show detailed time‐course for platelet fluctuation. Our case emphasis attention to monitor see‐saw‐like toxicity on platelet count. Abstract: Gemcitabine induce thrombocytopenia and thrombocytosis as toxicity. In this report, we show detailed time‐course for platelet fluctuation. Our case emphasis attention to monitor see‐saw‐like toxicity on platelet count.